2007
DOI: 10.1002/chin.200752043
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Sulfides to Sulfoxides Catalyzed by Ruthenium (III) meso‐Tetraphenylporphyrin Chloride in the Presence of Molecular Oxygen.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…There are at least three reasons that strongly inspired us to choose metalloporphyrins as the organic building block. First, as a biomimetic model of cytochrome P450 enzyme, metalloporphyrins have received considerable attention due to their extremely high catalytic activity, especially in selective oxidation reactions, including olefin epoxidation, sulfides oxidation, alcohol oxidation, and Baeyer‐Villiger reaction . It can be expected that hybrid flowers composed of metalloporphyrins will show equally superior catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…There are at least three reasons that strongly inspired us to choose metalloporphyrins as the organic building block. First, as a biomimetic model of cytochrome P450 enzyme, metalloporphyrins have received considerable attention due to their extremely high catalytic activity, especially in selective oxidation reactions, including olefin epoxidation, sulfides oxidation, alcohol oxidation, and Baeyer‐Villiger reaction . It can be expected that hybrid flowers composed of metalloporphyrins will show equally superior catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The largest bulk of reports have been with Mn(III), Fe(III), Ru(III), Co(III) and Cr(III) porphyrins, in that order. Among them, Mn(III), Fe(III), Ru(III) and Co(III) porphyrins have been found to be efficient catalysts for www.intechopen.com the mono-oxygenation of alkanes, the epoxidation of simple olefins and the oxidation of sulphides, while Cr(III) porphyrins be competent only for epoxidation Zhou et al, 2007). An enormous range of oxidants have been used as oxygen donors to the metalloporphyrins, including iodosobenzene, peroxyacids, hypochlorite, chlorite, hydroperoxides, N-oxides, hydrogen peroxide, monoperoxyphthalate, potassium monopersulfate and molecular oxygen (or air).…”
Section: Synthetic Metallo-porphyrinsmentioning
confidence: 99%
“…[10] Recently we have found that metalloporphyins exhibited highly catalytic performance for oxidation of alkanes, [11] olefins, [12] sulfides, [13] alcohols, [14] and aldehydes [15] with molecular oxygen. However, the conventional synthesis of porphyrin and its derivatives [16] is time-consuming.…”
Section: Xing-chuan Wei C Yun-quan Deng a And Kun Zhangmentioning
confidence: 99%